Facile synthesis of 1,3-thiazolidin-4-ones as antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Arkile, Manisha A.; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
We have developed, highly efficient, one-pot, solvent-free, [Et3NH][HSO4] catalyzed multicomponent reaction protocol for the synthesis of 1,3-thiazolidin-4-ones in excellent yields. For the first time, the 1,3-thiazolidin-4-ones were evaluated in vitro for their antimycobacterial activity against Mycobacterium tuberculosis dormant MTB H37Ra and Mycobacterium bovis BCG strains. Among the synthesized basic 1,3-thiazolidin-4-ones, particularly the compounds 4c, 4d, 4e, 4f, 4h, 4i and 4j displays promising antitubercular activity along with no significant cytotoxicity against the cell lines MCF-7, A549 and HCT-116. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular; Cytotoxicity; Green protocol; Multicomponent reaction

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives